A hybrid impulsive and sampled-data control framework for a class of nonlinear dynamical systems with input constraints. (May 2020) - Li, Hongfei; Li, Chuandong; Huang, Junjian
Abstract: In this article, a new hybrid controller is designed, which consists of sampled-data controller and impulsive controller with actuator saturation. Firstly, by applying polytopic representation approach and establishing an appropriated Lyapunov function, some established linear matrix inequalities (LMIs) are obtained to guarantee exponential stabilization of a class of nonlinear dynamical systems. It is worth mentioning that these LMIs are very easy to verify by the Matlab LMI toolbox. Moreover, based on sector nonlinearity model approach, sufficient conditions ensuring exponential stabilization are established by LMIs. Furthermore, it is also shown that a hybrid controller without actuator saturation and under same assumptions can achieve exponential stabilization of a class of nonlinear dynamical systems. Finally, three examples are provided to show the effectiveness of theoretical analysis.